2010
DOI: 10.1080/02687038.2010.489256
|View full text |Cite
|
Sign up to set email alerts
|

Chance in agrammatic sentence comprehension: What does it really mean? Evidence from eye movements of German agrammatic aphasic patients

Abstract: Background: In addition to the canonical subject-verb-object (SVO) word order, German also allows for non-canonical order (OVS), and the case-marking system supports thematic role interpretation. Previous eye-tracking studies (Kamide et al., 2003;Knoeferle, 2007) have shown that unambiguous case information in non-canonical sentences is processed incrementally. For individuals with agrammatic aphasia, comprehension of non-canonical sentences is at chance level (Burchert et al., 2003). The trace deletion hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
114
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(136 citation statements)
references
References 41 publications
(69 reference statements)
15
114
4
2
Order By: Relevance
“…Mack et al (2013) showed that eye movements of IWAs indicate delayed lexical access during sentence comprehension compared to age-matched healthy adults. Previous studies found that when IWAs interpreted non-canonical sentence structures correctly, eye movement patterns were similar to those of NBDs (passives: Dickey and Thompson, 2009; object-verbsubject sentences: Hanne et al, 2011), although competition with incorrect referents of a clause was sometimes increased towards the end of the sentences (object wh-questions: Dickey et al, 2007;object relatives: Dickey and Thompson, 2009;pronominal reference: Choy and Thompson, 2010). In a study by Meyer et al (2012), 5 eye movement data demonstrated that compared to NBDs, IWAs are delayed in processing active and passive sentences even when their offline response (in a sentence-picture matching task) was correct.…”
Section: Aphasiological Eye-tracking Studiesmentioning
confidence: 63%
See 1 more Smart Citation
“…Mack et al (2013) showed that eye movements of IWAs indicate delayed lexical access during sentence comprehension compared to age-matched healthy adults. Previous studies found that when IWAs interpreted non-canonical sentence structures correctly, eye movement patterns were similar to those of NBDs (passives: Dickey and Thompson, 2009; object-verbsubject sentences: Hanne et al, 2011), although competition with incorrect referents of a clause was sometimes increased towards the end of the sentences (object wh-questions: Dickey et al, 2007;object relatives: Dickey and Thompson, 2009;pronominal reference: Choy and Thompson, 2010). In a study by Meyer et al (2012), 5 eye movement data demonstrated that compared to NBDs, IWAs are delayed in processing active and passive sentences even when their offline response (in a sentence-picture matching task) was correct.…”
Section: Aphasiological Eye-tracking Studiesmentioning
confidence: 63%
“…Recently it has been shown that eye-tracking studies applying the visual-world paradigm (Allopenna et al, 1998;Cooper, 1974; for a review of visual world studies see Huettig et al (2011)) can provide insights into language processing in non-brain-damaged speakers, as well as in the online and behavioral performance of aphasic individuals (Dickey et al, 2007;Dickey and Thompson, 2009;Hanne et al, 2014Hanne et al, , 2011Meyer et al, 2012;Mack et al, 2013;Thompson and Choy, 2009; for a review on aphasiological visual-world studies see Burchert et al (2013)). This technique can clarify what occurs when time reference is interpreted incorrectly in agrammatic aphasia, and whether processing mechanisms differ per time frame.…”
Section: Introductionmentioning
confidence: 96%
“…Theme arguments appear to be inherently salient and show a strong advantage in anaphora resolution tasks (Stevenson, Crawley, & Kleinman, 1994), and the theme immediately precedes the preposition, which may confer a recency advantage. Regardless of which of these explanations of the theme preference for PWA is ultimately correct, this pattern is another example of PWA choosing a salient but grammatically impermissible interpretation when sentence comprehension fails (Dickey & Thompson, 2009;Hanne, Sekerina, Vasishth, Burchert, & De Bleser, 2011). Because participants tended to inhibit attention to this tempting distractor more in the argument condition than they did in the adjunct condition and because that tendency was numerically related to both verb-comprehension performance and conceptual-semantic knowledge regarding actions, individuals with aphasia may use verb-related information in some capacity during processing, but doing so does not aid them in identifying the desired target.…”
Section: Discussionmentioning
confidence: 99%
“…Accessing all of the critical words prior to establishing these types of relationships provides semantic cues to support the effort of interpreting the sentence. This alternate reading strategy could be used to compensate for slowed lexical access (e.g., Thompson & Choy, 2009) or slowed or inefficient syntactic processing (e.g., Hanne, Sekerina, Vasishth, Burchert, & De Bleser, 2011).…”
Section: Discussionmentioning
confidence: 99%